The Influence of Fear on the Dynamics of Harvested Prey-Predator Model with Intra-Specific Competition - Ibrahim, Hiba Abdullah; Shalan, Rehab Noori; Aljaf , Dina (Iraqi Journal of Science, 2025)
The influence of fear on the dynamics of harvested prey-predator model with intra-specific competition is suggested and studied, where the fear effect from the predation causes decreases of growth rate of prey. We suppose that the predator attacks the prey under the Holling type IV functional response. he existence of the solution is investigated and the bounded-ness of the solution is studied too. In addition, the dynamical behavior of the system is established locally and globally. Furthermore, the persistence conditions are investigated. Finally, numerical analysis of the system is carried out.